2002
DOI: 10.1038/nrd873
|View full text |Cite
|
Sign up to set email alerts
|

Drugs targeting the renin–angiotensin–aldosterone system

Abstract: Effective antihypertensive therapy has made a major contribution to the reductions in the morbidity and mortality of cardiovascular disease that have been achieved since the 1960s. However, blood-pressure control with conventional drugs has not succeeded in reducing cardiovascular disease risks to levels seen in normotensive persons. Drugs that inhibit or antagonize components of the renin-angiotensin-aldosterone system are addressing this deficiency by targeting both blood pressure and related structural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
347
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(355 citation statements)
references
References 101 publications
1
347
0
7
Order By: Relevance
“…2,4 Indeed, the pharmacokinetics of ARBs in human bodies, specifically factors such as bioavailability, half-life duration and route of elimination, differ considerably between different ARBs. These different degrees of efficacy possessed by ARBs are based on differences in their chemical structures, which determine their unique pharmacological properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4 Indeed, the pharmacokinetics of ARBs in human bodies, specifically factors such as bioavailability, half-life duration and route of elimination, differ considerably between different ARBs. These different degrees of efficacy possessed by ARBs are based on differences in their chemical structures, which determine their unique pharmacological properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical trials have indicated that ARBs provide cardiovascular protection that extends beyond blood pressure lowering. 2 Treatment with ARBs effectively prevents cardiac hypertrophy and improves cardiovascular outcomes in patients with hypertension. 2,3 Structurally, most ARBs have a common biphenyl-tetrazole ring and unique side chains, which contribute to drug-specific differences in their pharmacokinetic and pharmacodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of AT 1 Rs promotes proliferation, vasoconstriction, antinatriuresis, and salt appetite (20). AT 2 Rs antagonize many of the biological effects of AT 1 Rs by causing vasodilation, apoptosis, and prostaglandin release (21). AT 1 and AT 2 receptors are expressed at both apical and basolateral sides in the ASDN cells, although AT 2 R expression is considerably lower (22)(23)(24).…”
Section: Whereas Regulation Of Enac By Aldosterone Is Generally Accepmentioning
confidence: 99%
“…Excessive RAS activity is a major underlying cause of many pathological states because Ang II increases BP and exerts direct growth-promoting effects on tissues that lead to endorgan damage. [1][2][3] Indeed, RAS inhibitors, such as ACE inhibitors and angiotensin AT 1 -receptor blockers (ARBs), have proved to be highly successful treatments for hypertension, heart failure, and related cardiovascular disorders. 3 Because renin catalyzes the first and rate-limiting step of the RAS and has high specificity for its substrate, angiotensinogen, renin inhibitors offer the potential for blocking this complex hormonal system at its initial point of activation, with a low likelihood of side effects.…”
mentioning
confidence: 99%